Effect of gonadotrophic hormone on reproductive performance of an estrus cows - SHUKLA, M K; DABAS, Y P S (The Indian Journal of Animal Reproduction, 2023)
Turty lactating crossbred cows aged 5-8 years were divided into three groups consisting of 10 animals in each group. The first and second groups received 1000 and 1500 JU of PMSG, respectively and the third group (control) was injected with I ml of Normal Saline Solution. All the animals of treatment group I ( 1000 JU PMSG) and group II ( 1500 lU PMSG) showed ovulatory estrus at 3.89±0.8 I and 3.64±0.65 days, respectively following PMSG injection whereas none of the animals of the control exhibited any sign of heat throughout the study period. The subsequent estrous cycle length of the animals of the treated group were in the normal range. All the animals in estrus were inseminated with quality frozen semen along with an intramuscular injection of 1500 JU HCG. The animals of group I and II took 1.80±0.67 and 2.0±0.83 services for conception following treatment. Per cent examination 11 days post insemination revealed little or no superovulatory response.